Lupang hinirang, lupang tinubuan : mga sanaysay sa kritika, kasaysayan, at politikang pangkultura - San Juan, E. (Epifanio), Jr., 1938-; De La Salle University Publishing House (Manila : De La Salle University Publishing House, 2015)
Criticism and social aspects of Philippine literature.
Includes bibliographical references and index.
In Tagalog.
Keywords: Philippine literature -- History and criticism; Philippine literature -- Social aspects